Reinforced fixation of distal fibula fractures in elderly patients; A meta-analysis of biomechanical studies. (July 2016) - Dingemans, Siem A.; Lodeizen, Olivia A.P.; Goslings, J. Carel; Schepers, Tim
Abstract: Background: There is an increasing incidence of fragility fractures of the ankle in the elderly population. The open reduction and internal fixation of these fractures is challenging, due to reduced bone stock quality as a result of osteoporosis. Biomechanical studies have shown contradicting results using reinforced constructions in the fixation of fibular fractures. We therefore performed a meta-analysis of biomechanical studies on reinforced fixation of distal fibular fractures. Methods: A literature search was conducted utilizing three online databases considering biomechanical testing of different fixation techniques of distal fibular fractures. A meta-analysis was performed on two biomechanical outcome measures; torsional stiffness and torque to failure. Findings: In a total number of 13 studies 8 different reinforcement techniques were identified. Of these studies, six compared locked lateral plating with conventional lateral plating. There were no statistically significant differences between the locking and non-locking lateral plate for torque to failure or torsional stiffness. Locked plating strength was independent from bone mineral density in four studies. An antiglide plate proved to be biomechanically superior compared to a lateral plate in one study and to a locked plate in another. Interpretation: Locked lateral plates are not biomechanically superior to conventional lateral plates. However the strength of locked plating may be independent of bone mineral density and could make this technique more suitable in the fixation of severe osteoporotic fractures. Highlights: Locked lateral plates are biomechanically not superior to regular lateral plates. Locked plating could be independent of bone mineral density. An antiglide plate could be a cheap alternative in fixating fragility ankle fractures. Other viable techniques need to be evaluated biomechanically.